Peningkatan Kinerja Sumber Daya Manusia Dengan Memberi Motivasi dan Disiplin - Lia Nuraeni; Eman Sulaeman (Peneliti.net, 2023)
The purpose of this study is to analyze the influence of motivation, employee involvement and organizational culture on staff performance. The Central Java Provincial Cooperative Micro-SME Office has an important role and task in the formation or leadership of small and medium-sized micro-cooperatives, the scope of factors that can improve the efficiency of human resources in carrying out their tasks must be looked at 162 officials of small and medium-sized cooperatives in Central Java Province participated in this study, and 110 respondents participated in this study. The analysis results using multiple linear regression showed that motivation has a positive effect on organizational commitment and improving employee performance, and commitment has a positive effect on improving staff and applying the influence of organizational culture to moderate the current structure to achieve staff improvement. performance of resources.